Unburied bodies : subversive corpses and the authority of the dead - Martel, James R. (Public works (Amherst, Mass.), 2018)
The human body is the locus of meaning, personhood, and our sense of the possibility of sanctity. The desecration of the human corpse is a matter of universal revulsion, taboo in virtually all human cultures. Not least for this reason, the unburied corpse quickly becomes a focal point of political salience, on the one hand seeming to express the contempt of state power toward the basic claims of human dignity--while on the other hand simultaneously bringing into question the very legitimacy of that power. In Unburied Bodies: Subversive Corpses and the Authority of the Dead, James Martel surveys the power of the body left unburied to motivate resistance, to bring forth a radically new form of agency, and to undercut the authority claims made by state power. Ranging across time and space from the battlefields of ancient Thebes to the streets of Ferguson, Missouri, and taking in perspectives from such writers as Sophocles, Machiavelli, Walter Benjamin, Hannah Arendt, Judith Butler, Thomas Lacqueur, and James Baldwin, Martel asks why the presence of the abandoned corpse can be seen by both authorities and protesters as a source of power, and how those who have been abandoned or marginalized by structures of authority can find in a lifeless body fellow accomplices in their aspirations for dignity and humanity.